Określenia nieostre i klauzule generalne jako wyraz elastyczności prawa podatkowego — zarys problematyki - Borszowski, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Over-regulation in the Polish tax law causes the need to look for mechanisms that mitigate this process. One of the important issues leading to searching for these mechanisms is the flexibility of the tax law. The issue of the flexibility of the tax law is further justified by the strong relationship between business transactions and tax law, which directly fits into the overall relationship between development of socio-economic reality and the development of the law. The flexibility of the tax law is expressed by conventional means of legislative technique, i.e., blurred definitions and general clauses. The legislature recognizes the need of the functioning in certain tax structures. However, the adopted solutions do not sufficiently take into account the purpose of the certain regulation of the tax law and the place of specific technique measures within the legislative regulations.
Keywords: niewyraźne definicje; klauzule ogólne; podatek